2016
DOI: 10.1080/10400435.2016.1208303
|View full text |Cite
|
Sign up to set email alerts
|

Value-based design for the elderly: An application in the field of mobility aids

Abstract: In the aging society, the need for the elderly to remain mobile and independent is higher than ever. However, many aids supporting mobility often fail to target real needs and lack acceptance. The aim of this study is to demonstrate how value-based design can contribute to the design of mobility aids that address real needs and thus, lead to high acceptance. We elicited values, facilitators, and barriers of mobility of older adults via ten in-depth interviews. Next, we held co-creation sessions, resulting in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 25 publications
0
20
0
1
Order By: Relevance
“…For example, Willard and colleagues (2018) observed that a majority of 73% did not consider the community platform they jointly developed to be of additional value. Also, the prototypes of different mobility aids created together with older adults in a study by Boerema and colleagues (2017) received a low rating on acceptance, both by older people already using similar devices and older persons not using any aids.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Willard and colleagues (2018) observed that a majority of 73% did not consider the community platform they jointly developed to be of additional value. Also, the prototypes of different mobility aids created together with older adults in a study by Boerema and colleagues (2017) received a low rating on acceptance, both by older people already using similar devices and older persons not using any aids.…”
Section: Resultsmentioning
confidence: 99%
“…All C-M participants should be equal, power imbalances should be addressed and solutions to problems should be address collaboratively. Around two thirds of included studies were researcher led and five did not explicitly state leadership (Boerema et al, 2016;Clarke et al, 2009;Holliday et al, 2015;Morrison & Dearden, 2013;Wang-Letzkus et al, 2012). Exceptions included studies that claimed to be 'stakeholder-led' (Bond et al, 2015) or guided and advised by a committee or project team (Bone et al, 2013;James, et al, 2015;Nguyen et al, 2019;Ralston et al, 2017).…”
Section: Equalmentioning
confidence: 99%
“…Third, the different information has distinct delivery requirements in situations of urgency or depending on high accuracy. The most popular audio interaction for assistive navigation systems [16,[26][27][28] suffers from the following aspects:…”
Section: Dual-channel Human-machine Interactionmentioning
confidence: 99%